Dynamic swallowing study for globus patients. Issue 4 (1st December 2016) - Li, Jinrang; Zhang, Jie; Guo, Pengfei; Tian, Shiyu; Li, Keliang
Abstract : Objective: To examine whether pharyngeal swallowing function is impaired in globus patients with swallowing difficulty by dynamic swallowing study. Methods: Dynamic swallowing studies were performed on 80 normal adult volunteers and 33 globus patients with swallowing difficulty. Objective parameters such as maximum displacement of the hyoid bone, pharyngeal transit time, pharyngeal constriction ratio, and maximum opening of the esophageal entrance were measured, which were closely associated with the pharyngeal swallowing function in the swallowing process. Results: There were no significant differences between globus patients and normal adults in hyoid bone displacement, pharyngeal transit time, pharyngeal constriction ratio, or maximum opening of the esophageal entrance ( p  > 0.05). Conclusion: The results of the dynamic swallowing study indicated that the pharyngeal swallowing function of globus patients was not impaired.